Quantifying Stability in Inverter-Based Weak Grids in the Presence of Synchronous Condensers - Sajjad Hadavi; Nabil Mohammed; Ali Mehrizi-Sani; Behrooz Bahrani (IEEE Open Access Journal of Power and Energy)
The high penetration of renewable energy resources, integrated via power electronic inverters, into weak and low-inertia grids has led to the emergence of new challenges within power systems. The absence of native inertia in inverter-based resources (IBRs), in contrast to fossil-fuel-based generators, can result in sustained oscillations and instability. Synchronous Condensers (SynCons) are being considered as a reborn technology to address the challenges associated with system strengthening and inertia support in IBR-dominant power systems. Despite the well-established nature of SynCons, an additional assessment is necessary to analyze the stability of a weak grid with a high penetration of renewable resources, particularly in the presence of SynCons. This paper proposes a quantitative index for the stability analysis of a system incorporating black-boxed IBRs and SynCons. The proposed index is derived from impedance-based stability analysis. The impact of a SynCon on the proposed stability index is evaluated in a single-machine infinite-bus system, and its accuracy is further verified in an IEEE 39-bus system. Additionally, the findings are corroborated through time-domain simulation tests conducted in PSCAD/EMTDC software.